Karakteristik Kemampuan Siswa SMA dalam Menyelesaikan Well dan Ill Structured Problems pada Pembelajaran Fisika - Supeno Supeno; Sri Handono Budi Prastowo; Marlina Puji Rahayu (Department of Physics Education, Universitas Mataram, 2020)
One effort to improve the quality of learning physics is by developing abilities in problem solving. Problem solving abilities are complex cognitive activities using thought processes. For students, by knowing problem solving abilities, they can do self-reflection and have learning motivation to change for the better. For teachers, knowing students' abilities in problem solving can be used as a guide for designing learning strategies and evaluations that are suitable for improving problem solving skills. For this reason, it is necessary to identify problem solving abilities of high school students. Methods of research data collection using tests and interviews. Tests for measuring problem solving abilities are categorized as ill-structured problems and well-structured problems. The results showed that students were better able to solve well-structured problems than ill-structured problems. The ability of students to solve well-structured problems and ill-structured problems, most of them are included in the category of novice and only a small proportion are categorized as expert. The novice and expert characteristics based on the results of the study is described in detail in the part of discussion.